Evaluating Science-Technology-Society (STS) approach in teaching high school science - Fornias, Virginia Ramos (Animo Repository, 2002)
This study evaluates the efficacy of Science-Technology-Society (STS) Approach in teaching high school science. Such evaluation focused on the development of science process skills, higher order thinking skills, environmental awareness and cooperative learning skills of students in all year levels. The respondents were high school students of St. Scholastica's College, Manila, during school year 2001-2002. Self-made pencil-and-paper multiple-choice tests were given to science teachers and experts for content and face validation. They were likewise administered to the students specifically for their comments and in determining the time at which they could be able to finish the test. Considering all comments and suggestions, revisions were made. Revised questionnaires were then administered to the target respondents for pretest and posttest. Validation focused only on content since the instruments are for St. Scholastica's College High School Department purpose only. Hence, the main goal is to look at the instruments' consistency with the instructional and program objectives of the department. There were 20 items for science process skills test for year 1 (SPST 1), 20 for year 2 (SPST 2), 20 for year3 (SPST 3), and 20 for year 4 (SPST 4) 20 items for higher oder thinking skills test (HOTST) for all year levels 20 items for environmental awareness test (EAT) for all year levels. For cooperative learning skills test (CLST) for all year levels, a scale type of test was given with options frequent , sometime , and never as their responses for each item. Results were analyzed using t-test for significant difference. Analyses of results revealed that the STS Approach was effective in developing higher order thinking skills of students in all year levels but has been effective in developing science process skills of 3rd and 4th year students. However, the approach was found to be not effective in developing environmental awareness and cooperative learning group skills of students in all year levels. Nevertheless, it could not discount the fact that certain science process skills have also been acquired by the students in 1st and 2nd year levels; and certain cooperative learning group skills were manifested by the students in all year levels as a result of their exposure to the approach.